Nursing Development in Indonesia: Colonialism, After Independence and Nursing act - I Gede Juanamasta BNS, MNS; Abdulkareem S. Iblasi BNS, MNS, PhD (c); Yupin Aungsuroch PhD, RN; Jintana Yunibhand PhD, RN (SAGE Publishing, 2021)
Introduction Stereotyping of nurses still occurs nowadays in Indonesia. Society and healthcare think nursing is a doctor helper service. The public image of a nurse as a doctor's helper is hard to erase. Thus, the nursing development in Indonesia needs to be explored in describing the stereotyping and the nursing conditions in the current situation. Methods The study used a narrative review with 45 sources analyzed and extracted. Results Nursing education has been developed since colonialism. The first time the Netherland Indies built the hospital and they used Babu or a helper as a nurse. The result showed it had a negative impact, which showed as they started to train nurses. They trained male nurses to be Mantri nurses as hulpgeneesheeren (ancillary doctors). After independence, the project HOPE influenced the development of nursing in Indonesia. Indonesian nurses focused on technical aspects and added the nursing process to the education curricula in 1986. However, nurses' practice culture did not change for a long time because of a lack of research and literature being evaluated during 1990-2010. Indonesia nursing started to increase the education, practice, and research afterward, with specifically the declaration of the Indonesian Nursing Act. It brought nurses into the professionalism of healthcare which the Indonesian government recognized. Then, nurses have faced new problems, including practice and education gaps. Conclusion The development of nurses will increase autonomy and dignity. Increasing education curricula, practice competency, and research impact will change the perspective of society with the support of recognition and education from the nursing organization. In addition, the nursing organization has an essential role in nursing development in each country.